2009
DOI: 10.1097/prs.0b013e3181b5a3c3
|View full text |Cite
|
Sign up to set email alerts
|

Tibial Nerve Decompression in Patients with Tarsal Tunnel Syndrome: Pressures in the Tarsal, Medial Plantar, and Lateral Plantar Tunnels

Abstract: Many surgeons operating on patients with tarsal tunnel syndrome do not decompress the respective medial plantar and lateral plantar nerves and excise the septum. The authors' study validates the hypotheses that patients who are clinically suspected of having chronic compression of the tibial nerve and its branches at the ankle have higher tunnel pressures and that releasing these structures decreases the pressures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(72 citation statements)
references
References 36 publications
1
66
0
5
Order By: Relevance
“…At least six studies have confirmed ND can provide significant, although not total protection against DFU and recurrence [17,2125]. Studies also exist using as outcomes perineural tissue pressure [18], transcutaneous oxygen pressures [37], and measured balance [56,72]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At least six studies have confirmed ND can provide significant, although not total protection against DFU and recurrence [17,2125]. Studies also exist using as outcomes perineural tissue pressure [18], transcutaneous oxygen pressures [37], and measured balance [56,72]. …”
Section: Discussionmentioning
confidence: 99%
“…Such levels are expected to affect vasa nervorum circulation and neural axoplasmic flow. With ND, intra-operative pressures return to normal levels under 10 mm [18]. …”
Section: Objective Outcomesmentioning
confidence: 99%
“…Ducic and coauthors 41 reported bilateral ND improves balance as measured by sway, and Rosson and coauthors 35 found perineural tunnel pressures, so high as to threaten tissue survival, returned to safe levels after ND. In 75 DSPN legs with prior ulcer, of IWGDF group 3, after ND, ipsilateral DFU recurrence risk is >80% reduced from historical values.…”
Section: The Entrapment Hypothesismentioning
confidence: 99%
“…2,30,31 Objective outcome studies and prospective or randomized controlled trial protocols now report beneficial ND effects on balance, tunnel tissue pressures, ulceration risk, DFU recurrence risk, and electrophysiological parameters, as Figure 2 shows. [32][33][34][35][36][37][38][39] These often include and correlate common subjective measures of DSPN symptoms and signs. Aszmann and coauthors 32 first published the unanticipated finding that every ulceration and amputation in 50 DSPN cases that had unilateral ND surgeries for leg pain occurred in the contralateral, nonoperated legs.…”
Section: The Entrapment Hypothesismentioning
confidence: 99%
“…Using a graded compression, it was noted that at pressures of 20-30 mmHg, axonal transport was blocked. According to Rosson et al, 40 perineural tissue pressures of 26 mmHg are recorded in diabetes patients with focal nerve entrapment in the foot. Additional work by Dahlin and McLean 41 in a rabbit model reported similar effects in both slow and fast axonal transport.…”
Section: Nerve Compression Functional Studiesmentioning
confidence: 99%